Coordinate imaging method - Esmukhan Zh.M. , Есмухан Ж.М.; Masimbayev E.E. , Масимбаев Е.Е. (Рroblems of engineering and professional education, 2023)
Widespread image projection method Was not convenient applied in computer graphics. Therefore, coordinate method is suggested, by constructiong the image of an object from the coordinates of its defining points.